RIGHT TO INFORMATION ACT: AS A MECHANISM TO FIGHT AGAINST CORRUPTION TO PROMOTE GOOD GOVERENCE IN INDIA - Dr. Pooja (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
India is a democratic country and in every democratic country, there is a need of good governance and transparency. In every development administration experiences indicated that there has always an urgent need for improving government .Today in India there is unprecedented corruption at all levels. All feel its squeeze but corruption is roaring high. The main factor behind the corruption is secrecy, which was taken as a tool of accuracy towards government in past era. If we want transparency in governance, there is a need to crack the corruption by cracking the walls of secrecy. This paper tries to highlight the RTI as a vital tool in the reduction of Corruption and some steps for the development of democratic governance. In this article the study is based on Secondary sources, which includes books, journals, reports, news papers, internet websites, government publications and records.